2019
DOI: 10.1557/adv.2019.415
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Laser Welding Sequences on Residual Stresses and Distortion of DP600 Steel Joints

Abstract: Different materials have been welded by laser beam. This process allows to obtain high quality welds with lower thermal effect. Laser beam welding produces narrow and high penetration welds without filler material. However, this process modifies the mechanical and microstructural properties of the welded joints. Therefore, this is currently a research topic, mainly using Advanced High Strength Steel (AHSS). These materials are used in the automotive industry. As a result, it is important to study the thermomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Laser welding of thin DP steel plates induces more intense residual stresses in the longitudinal direction (weld axis), with tensile stresses close to material yield strength at the center of the weld, which progressively decrease and become slightly compressive at base material. In the transverse direction, residual stresses present a similar pattern, tensile at the center and compressive at the edges of the weld, although at lower levels when compared to the longitudinal ones (up to 8 times lower) ( Carrizalez-Vazquez and Pérez-Medina, 2019 ).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Laser welding of thin DP steel plates induces more intense residual stresses in the longitudinal direction (weld axis), with tensile stresses close to material yield strength at the center of the weld, which progressively decrease and become slightly compressive at base material. In the transverse direction, residual stresses present a similar pattern, tensile at the center and compressive at the edges of the weld, although at lower levels when compared to the longitudinal ones (up to 8 times lower) ( Carrizalez-Vazquez and Pérez-Medina, 2019 ).…”
Section: Introductionmentioning
confidence: 97%
“…These simulations can partially replace experimental sample tests, lowering project costs. By optimizing the welding parameters, they provide better quality to the welded products, avoiding misalignment and unexpected failures during operation ( Carrizalez-Vazquez and Pérez-Medina, 2019 ). Some works have pointed out as the most important aspects of laser welding simulation the introduction of metallurgical transformations in the model and the correct keyhole representation ( Tsirkas et al., 2003 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results show that the welding direction has an insignificant influence on the welding deformation, and the welding deformation appears to mainly depend on the welding consumable volume. Carrizalez-Vazque and Pérez-Medina [9] simulated the welding process of butt joints made of DP600 steel thin plate considering different welding sequences. It was found that the welding residual stress and deformation caused by the segmented continuous welding were much smaller compared to the single-pass welding under the same heat input.…”
Section: Introductionmentioning
confidence: 99%
“…Satish et al [25] found that significant differences in the threedimensional temperature distribution and residual stress state in AISI304L stub T-joints with different tube sizes along different cross sections. Carrizalez-Vazquez et al [26] used laser welding of butt joints of DP600 steel plates and reduced the deformation and residual stresses in the specimens by adjusting the welding sequence. Wang et al [27] found that a slower welding speed and Case B welding sequence resulted in more symmetrical welding.…”
Section: Introductionmentioning
confidence: 99%